2015
DOI: 10.2174/1573396311666150501003435
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Factors Associated With Low Aerobic Performance Levels in Adolescents: A Systematic Review

Abstract: Low aerobic performance levels have been considered one of the risk factors for premature mortality, regardless of presence of other health problems. The critical analysis of studies on the prevalence of low aerobic performance and associated factors may contribute to the epidemiological knowledge and analysis / discussion of socio-cultural aspects that influence low aerobic performance. The aim of this systematic review was to identify studies on the prevalence of low aerobic performance levels and possible a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 0 publications
2
18
0
1
Order By: Relevance
“…The present study showed that obese individuals had lower cardiorespiratory fitness which is in accordance with the previous study [26]. Underweight children and adolescents performed superior to obese individuals between four BMI categories because the lower weight of underweight adolescents is helpful in endurance running.…”
Section: Discussionsupporting
confidence: 92%
“…The present study showed that obese individuals had lower cardiorespiratory fitness which is in accordance with the previous study [26]. Underweight children and adolescents performed superior to obese individuals between four BMI categories because the lower weight of underweight adolescents is helpful in endurance running.…”
Section: Discussionsupporting
confidence: 92%
“…The best explanatory power of the sum of three skinfolds for predicting VO 2 max may indicate that the analysis of different sites of fat accumulation results in increased accuracy to estimate total fat and consequently lean body mass in different individuals (14). A review study showed that individuals with excess body fat had low aerobic fitness levels, regardless of protocol used to assess excess adiposity (BMI, body fat percentage, waist circumference, sum of skinfolds and CI) (31). Furthermore, it was found that large amounts of lean body mass was related to suitable aerobic fitness values due to the oxidative potential of muscle fibers (32).…”
Section: Discussionmentioning
confidence: 99%
“…The decline in aerobic fitness is associated with some individual characteristics, such as sociodemographic and life style factors. 6 A systematic review identified the following factors associated with low levels of aerobic fitness: female gender, low economic level, lower consumption of dairy products and cereals, higher consumption of sweetened beverages, insufficient physical activity, excessive screen time and excess of body fat. 6 However, it is controversial the association between low levels of aerobic fitness and other sociodemographic factors, such as skin color and age.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the association between aerobic fitness levels and excessive alcohol and tobacco consumption is scarcely studied. 6 …”
Section: Introductionmentioning
confidence: 99%